Dauru al-Ummawiyyin fi Muwajahah al-Byzantins - Hussein Ali Mahafzah (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2017)
This studyâ€ â€â€Ž amis to discuss the role of the Ummayads in meeting the Byzantins â€Žmilitarily in terms of their role to open the levant and its management on the one â€Žhand and the establishment of their state and the evolution of its conflict with â€Žthe Byzantines on the other hand. First the practice of defense policy and â€Žsecondly attack. Then switch to planned defense plans to suit the conditions and â€Žcircumistances. The study has concluded that there is distinct military pivotal â€Žrole at the Ummayad Caliphs in their struggle with the Byzantines. The current â€Žacademic considered this a superiority in the light of what has preceded and â€Žfollowed it. â€Ž